Selection signatures detection in Nelore, Gir, and Red Sindhi cattle breeds - Genuíno, Maria Victória Henrique; Bessa, Ayrton Fernandes de Oliveira; da Silva, Roney Teixeira [UNESP]; Câmara, Giovanna Maria dos Santos [UNESP]; Panetto, João Cláudio do Carmo; Machado, Marco Antônio; Caetano, Sabrina Luzia [UNESP]; Ramos, Salvador Boccaletti [UNESP]; Munari, Danísio Prado [UNESP]; Sonstegard, Tad; Barbosa da Silva, Marcos Vinícius Gualberto; Buzanskas, Marcos Eli [UNESP] (Springer Nature, 2025)
Technological advances in genomics and bioinformatics made it possible to study the genetic structure of breeds and understand genome changes caused by selection over generations. Our objective was to evaluate selection signatures (SS) in Nelore, Gir, and Red Sindhi cattle from Brazil and the Asian continent to identify divergent variants due to the history of formation and selection of populations, with a focus on the SS of animals from Brazil. Extended haplotype homozygosities between populations (XP-EHH), the ratio of site-specific extended haplotype homozygosity between populations (Rsb), and the allelic fixation index (Fst) were used to detect SS. Considering a window size of 50-kb, a non-sliding window approach was used to define SS regions. A total of 62, 57, and 72 genes were co-located within SS regions for Nelore, Gir, and Red Sindhi, respectively, and used to perform functional analyses per breed. Most genes were associated with productive and reproductive traits, while others were related to thermotolerance, the immune system, temperament, and coat color. The identified SS demonstrate how animal breeding programs shape the genetic makeup of these breeds to meet production system requirements, given that animals from Brazil and the Asian continent have undergone different selection processes. The identification of genes related to thermotolerance, temperament, and the immune system suggests specific alleles have enabled animals to adapt to environmental conditions and selection criteria in Brazil. Understanding SS can support breeding strategies for Nelore, Gir, and Red Sindhi cattle, contributing to enhanced resistance, adaptation, and productivity to meet food production demands.
Keywords: Adaptation genetics; Genetic selection; Haplotype analysis; Heat tolerance genes; Livestock genomics; Zebu cattle